Microestrutura e caracterização dielétrica em radiofrequência e micro-ondas da cerâmica Fe2Mo3O12 - Araújo, Eduardo Viana de (2019)
The electroceramics emerged as an option to integration and miniaturization of electronic circuits, making the smaller and more efficient systems, which can be applied as dielectric resonator antenna, capacitors, among others. The great challenge on it integration is due its high sintering temperature, that hinders the integration of these metallic components in circuit due the metal melting on process. After some tests, it was discovered that the addition of low melting oxides, or some glassy phases could be used to decrease the sintering temperature of ceramic. The LTCC (Low Temperature Cofired Ceramics), are materials which show sintering temperatures lower than melting temperature of some metals used in circuits. Among them, the molybdates are widely explored and its efficiency were reported in some works. Although they are widely explored and widespread, the iron molybdate III (Fe2Mo3O12) is a LTCC too and its dielectric behavior wasn’t properly explored. The Fe2Mo3O12 was synthesized by solid state route and characterized by x-ray diffraction, Raman spectroscopy, Mössbauer spectroscopy and scanning electronic microscopy (SEM) techniques. These techniques’ results showed the great efficiency to reach desirable phase. To determine dielectric properties with temperature, the samples were prepared with different concentrations of sintering aid based in Bi2O3-B2O3 mix. The activation energy (Ea) for each composition showed a sintering aid concentration dependency, which values are between 0.650 and 0.952 eV. The microwave properties were studied; FMO and FMO 7.5% were the pellets, which presented lower values of temperature coefficient of resonant frequency (τf) of -6.55 and -4.35 ppm/°C respectively. The values of dielectric constant were within 9.3 and 9.8 for all compositions while the dielectric loss (tan δ) are in 10-4 of magnitude order for all samples, which 9.452x10-4 was the higher for all pellets corresponding to FMO sample.